Measles immunity among pregnant women aged 15–44 years in Namibia, 2008 and 2010. (August 2016) - Cardemil, Cristina V.; Jonas, Anna; Beukes, Anita; Anderson, Raydel; Rota, Paul A.; Bankamp, Bettina; Gary, Howard E.; Sawadogo, Souleymane; Patel, Sadhna V.; Zeko, Sikota; Muroua, Clementine; Gaeb, Esegiel; et al.
Highlights: Thirteen percent of pregnant Namibian women are susceptible to measles. Nearly one in four 15–19-year-old pregnant women are susceptible to measles. A large measles outbreak did not significantly change the measles population immunity. In Namibia, measles vaccination should be considered for adults in order to achieve elimination. Summary: Background: Namibia experienced a large measles outbreak starting in 2009, with 38% of reported cases in adults, including women of reproductive age. Population immunity was assessed among pregnant women to determine whether immunization activities were needed in adults to achieve measles elimination in Namibia. Methods: A total of 1708 and 2040 specimens sampled from Namibian pregnant women aged 15–44 years who were included in the 2008 and 2010 National HIV Sentinel Survey, respectively, were tested for measles immunoglobulin G antibody. The proportion of women seropositive overall and by 5-year age strata was determined, and factors associated with seropositivity were analyzed by logistic regression, including age, facility type, gravidity, HIV status, and urban/rural setting. Seropositivity in 2008 versus 2010 was compared. Results: In both analysis years, measles seropositivity was lower in 15–19-year-olds (77%) and 20–24-year-olds (85–87%) and higher in 25–44-year-olds (90–94%) (2008, p < 0.001; 2010, p < 0.001). Overall measles seropositivity did not differ between 2008 (87%) and 2010 (87%) ( p = 0.7). HIV status did not affect seropositivity. Conclusions: Late in a large measles outbreak, 13% of pregnant women in Namibia, and almost one in four 15–19-year-old pregnant women, remained susceptible to measles. In Namibia, immunization campaigns with measles-containing vaccine should be considered for adults.